Identification of chlorohydrocarbon degradation pathways in aquitards using dual element compound-specific isotope measurements in aquifers. (September 2022) - Lincker, Manon; Lagneau, Vincent; Guillon, Sophie; Wanner, Philipp
Abstract: Compound-specific isotope analysis (CSIA) has been increasingly used to understand and quantify the (bio)degradation processes affecting chlorohydrocarbons in aquifer-aquitard systems. In this study, we aimed at investigating through reactive transport simulations if dual element (C, Cl) CSIA in aquifer samples can provide information about the occurring (bio)degradation pathways in the underlying aquitard. To that end, we modeled the continous dissolution of a 1, 1, 2, 2-tetrachloroethane (TeCA) dense nonaqueous phase liquid (DNAPL) source in an aquifer as well as the resulting TeCA groundwater plume formation and diffusion into the underlying aquitard. The (bio)degradation of TeCA in the aquifer-aquitard system was simulated in four scenarios: TeCA biodegradation via dehydrohalogenation to trichloroethene (TCE) and TeCA dichloroelimination to dichloroethene (DCE) in the aquifer as well as in the aquitard. The simulations revealed that dual element (C, Cl) CSIA in the aquifer allows the disentanglement of whether TeCA degradation occurs in the aquifer or the aquitard and which (bio)degradation pathways occur in the aquitard. This demonstrates that chlorohydrocarbon (bio)degradation pathways in aquitards can be identified based on CSIA aquifer measurements only, which is an advantage as aquifers are easier to monitor than aquitards. Graphical abstract: Image 1 Highlights: Development of 2D-numerical model of contaminated aquifer-aquitard system. Simulation of dual element (C and Cl) isotope fractionation. Distinct aquifer C and Cl isotope pattern for various aquitard degradation pathways. Aquifer C and Cl isotope analysis reveals aquitard degradation pathways.